Yogyakarta Guitar Orchestra (YGO): managing innovation and creativity in creative resource management for classical guitar education in Indonesia - Ari Palawi; Setyabudhi Rahardjo Situmorang; Raden Agustinus Arum Eka Nugroho (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
Many researchers are fascinated by creativity and innovation. The question of creative resources at the Yogyakarta Guitar Orchestra (YGO) becomes the primary topic to be discussed in this paper. The premise is that the innovation and creativity framework embedded in YGO's creative resources directly impacts and influences the creative process so that the role of creative resources becomes visible. The goal of this study was to establish a model for YGO's creative resource management to manage innovation and creativity effectively. The research method is grounded theory, with data collected via interviews, literature reviews, and photo documentation. The data analysis was conducted using the innovation paradigm and the creative resource management perspective on creativity. The study's findings include information about how YGO acts as an accelerator for creative resources in order to foster innovation and creativity. This contribution can assist policymakers in directing resources and actions toward YGO or similar communities in order to foster the future development of a high-quality innovation and creative ecosystem